[Hg4Te8(Te2)4]8−: A Heavy Metal Porphyrinoid Embedded in a Lamellar Structure. Issue 28 (6th June 2018) - Donsbach, Carsten; Reiter, Kevin; Sundholm, Dage; Weigend, Florian; Dehnen, Stefanie
Abstract: The use of ionic liquids (C n C1 Im)[BF4 ] with long alkyl chains ( n =10,  12) in the ionothermal treatment of Na2 [HgTe2 ] led to lamellar crystal structures with molecular macrocyclic anions [Hg8 Te16 ] 8− (1 ), the heaviest known topological relative of porphyrin. [Hg8 Te16 ] 8− differs from porphyrin by the absence of an electronic π‐system, which prevents a "global" aromaticity. Quantum chemical studies reveal instead small ring currents in the pyrrole‐type five‐membered rings that indicate weak local (σ) aromaticity. As a result of their lamellar nature, the compounds are promising candidates for the formation of sheets containing chalcogenidometalate anions. Abstract : Getting heavy : Ionothermal treatment of Na2 [HgTe2 ] with (C n C1 Im)[BF4 ] ( n =10, 12) affords salts with lamellar crystal structures of the macrocyclic anion [Hg8 Te16 ] 8− (1 ), the heaviest known topological relative of porphyrin. In accordance with its high structural flexibility, 1 does not exhibit a π‐electron system, but possesses small ring currents in the pyrrole‐type five‐membered rings, which indicates weak local (σ) aromaticity.